PENGARUH PENGELOLAAN LINGKUNGAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DENGAN PROFITABILITAS (ROA) PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empris pada Perusahaan Manufaktur yang Terdaftar di BEI - Putri, Suci Rahma; Ritonga, Kirmizi; Savitri, Enni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to determine the effect of environmental disclosure, institutional ownership toward corporate social responsibility disclosure (CSRD) with profitability (ROA) as a moderating variable. The population of this research is manufacturing company which is member of PROPER and listing in Indonesia Stock Exchange from 2011 to 2013. The research samples are 72 companies selected by using purposive sampling method. The statistical method used is multiple linear regression analysis. These results show that the impact of environmental disclosure and institutional ownership has significant impact toward corporate social responsibility disclosure. But, profitability (ROA) as the moderating variable in relation between environmental disclosure and institutional ownership toward corporate social responsibility disclosure has no significant impact.Keywords: environtmental, performance, ownership, ROA, CSRD.